Self-esteem of students who use social media - Bakri, Ahmad; Hidayat, Ahmad (World Psychology, 2024)
Individuals who like to socialize tend to build a positive self-image on social media to increase their self-esteem. Self-esteem is a self-evaluation formed by individuals by describing themselves both positively and negatively. Social media, which is a means of communication and interaction for every individual, also has a role in increasing a person's self-esteem. The aim of this research is to determine the self-esteem of students who use social media at the Faculty of Psychology, Riau Islamic University. This type of research is quantitative with a statistical descriptive approach. The scale used is a self-esteem scale consisting of 32 items. The number of samples used was 300 people using a non-probability sampling technique using the consecutive sampling method. The results of the research conducted in this study, if viewed as a whole, students who use social media have the highest self-esteem in the medium category, namely 127 people (42.3%), there is no difference in the level of self-esteem of students who use social media, both male and female. female, there is no difference in the level of self-esteem of students who use social media based on age and there is no difference in the level of self-esteem of students who use social media based on semester.